Routine HIV Screening in an Urban Community Health Center: Results from a Geographically Focused Implementation Science Program. - NUNN, AMY; TOWEY, CAITLIN; CHAN, PHILIP A.; PARKER, SHARON; NICHOLS, EMILY; OLESKEY, PATRICK; YOLKEN, ANNAJANE; HARVEY, JULIA; BANERJEE, GEETANJOLI; STOPKA, THOMAS; TROOSKIN, STACEY (Public Health Reports)
Objective. CDC has recommended routine HIV screening since 2006. However, few community health centers (CHCs) routinely offer HIV screening. Research is needed to understand how to implement routine HIV screening programs, particularly in medically underserved neighborhoods with high rates of HIV infection. A routine HIV screening program was implemented and evaluated in a Philadelphia, Pennsylvania, neighborhood with high rates of HIV infection. Methods. Implementation science is the study of methods to promote the integration of research findings and evidence into health-care policy and practice. Using an implementation science approach, the results of the program were evaluated by measuring acceptability, adoption, and penetration of routine HIV screening. Results. A total of 5,878 individuals were screened during the program. HIV screening was highly accepted among clinic patients. In an initial needs assessment of 516 patients, 362 (70.2%) patients reported that they would accept testing if offered. Routine screening policies were adopted clinic-wide. Staff trainings, new electronic medical records that prompted staff members to offer screening and evaluate screening rates, and other continuing quality-improvement policies helped promote screenings. HIV screening offer rates improved from an estimated 5.0% of eligible patients at baseline in March 2012 to an estimated 59.3% of eligible patients in December 2014. However, only 5,878 of 13,827 (42.5%) patients who were offered screening accepted it, culminating in a 25.2% overall screening rate. Seventeen of the 5,878 patients tested positive, for a seropositivity rate of 0.3%. Conclusion. Routine HIV screening at CHCs in neighborhoods with high rates of HIV infection is feasible. Routine screening is an important tool to improve HIV care continuum outcomes and to address racial and geographic disparities in HIV infection.